STUDENTS’ PERCEPTION OF ENGLISH LEARNING TOWARD THEIR CURRENT PROFESSION - Bobi Arisandi (British : Jurnal Bahasa dan Sastra Inggris, 2022)
Globalization era demands employees who have a proficient English skill so that international business activity can run well. University as a place which provides a skillful employee is forced to create a practical English learning. It means an English learning that can easily be applied in a workplace. However, it is not an easy task to bridge the demand and reality of teaching and learning in the classroom. Based on pre-observation, it is revealed that some of students were not able to implement the knowledge that they have learnt into their current work. They seem to face a difficulty in seeing the connection between what they learn and how to apply it into their job. Related to the issue, researchers plan to design a research entitled “Students’ Perception of English Learning toward Their Current Profession.” The research aims to find out students’ perception on what they learn related to English study and how it affects their current job or profession. The participant of this research were the seventh semester students of English Literature of Pamulang University. They were chosen as participants using purposive sampling. This research itself was conducted at English Letters Department of Pamulang University which is located at Jalan Raya Viktor, Pamulang, South Tangerang, Banten from December to January 2020-2021. In conducting this research, qualitative research was chosen as research design. There was one type of data collecting techniques which is questionnaire. The data were analyzed simultaneously using Creswell’s (2007) theory called data analysis spiral in order to get a strong and comprehensive conclusion toward the issue. Key words: current profession, English learning, students’ perception